EXTENDED DETERRENCE: CONCEPT, CHALLENGES AND PROBLEMS - Pejić, Igor (National interest, 2024)
This paper addresses the challenges faced by states in implementing the strategy of extended deterrence. Unlike direct deterrence, extended deterrence involves the participation of an additional actor, which makes political and military calculations more complex, thereby impacting the success of the strategy. As with direct deterrence, in extended deterrence, the issue of credibility is a central theme that often determines the strategy’s success and the way states prepare for potential threats. For a potential aggressor, credibility pertains to the political will and resources of the potential victim and its allies to defend it. On the other hand, for the defending state, credibility depends on the political intentions of its allies to protect it from a potential aggressor. Ultimately, major allies can manipulate various political tools to influence the policy of a potential aggressor, as well as the policy of smaller allies. The relationships between these actors and the perception of political intentions represent a key issue that leads to various dilemmas within the extended deterrence strategy. To explain the challenges and issues of extended deterrence, the paper analyzes various historical events. For instance, in the case of the Crimean War, unclear political intentions towards the Ottoman Empire, as well as mutual doubts between Great Britain and France, failed to deter Russia from its military campaign against the “sick man of the Bosphorus”. Strategic ambiguity, or ambivalence, which directly impacts the credibility of deterrence, is an important tool of great power politics, as evidenced in the case of Taiwan and the United States. By maintaining an ambiguous policy toward Taiwan, Washington allows continued cooperation with China while simultaneously keeping China uncertain about the U.S. response to a potential invasion of Taiwan. In this text, we also examine the challenges faced by small states and the dilemmas confronted by major allies. The relationships between these actors can often come at the expense of smaller allies. For small states, a high level of trust in a major ally can create space for them to engage in risky geopolitical ventures, which may harm the interests of the great powers. On the other hand, small states often hesitate in their relations with larger allies, fearing that “settling accounts” with other major powers may work to their disadvantage. The relationships between Washington, Tokyo, Seoul, and Taipei during the Cold War offer excellent examples of various alliance dilemmas and the policies these states used to reconcile divergent interests. The cases of the United States and its distant allies reveal the overlap between extended deterrence strategies and power projection. In Washington’s case, these strategies are complementary and often mutually reinforcing, which simplifies matters for American allies while sowing doubt among U.S. rivals. Ultimately, these contradictions impact the success of the strategy, leading some scholars to argue that deterrence is an art, not a science.